SPECTRAL LINE PROFILES VARIATIONS IN THE roAp STAR ALPHA CIRCINI - Alentiev, D. V. (Одеські астрономічні публікації, 2012)
We analyse behavior of the line profile variations of the brightest known roAp star αCircini based on the high-resolution spectra obtained with the HARPS spectrometer. The rapid variations of Nd and Pr line profiles are similar to other roAp stars.